Assessment of the impact of corruption on trade in oil exporting countries - Dolayeva, Zhuldyz (2020)
The aim of this research is to understand the impact of corruption on trade in oil exporting countries. We consider the possibilities and outcomes of corruption and the effect of corruption on trade. Using a panel data set for 10 countries over the period 2000-2018, this study contributes to the area of trade and corruption in oil exporting countries. The first part of this study exposes the causes of corruption and presents a literature review of many authors concerning corruption and trade in oil exporting countries. The second part reviews the methods and exposes the construct of an econometric model for the estimation of the impact of corruption. Using a panel data set for 10 countries over the period 2000-2018, this study contributes to the area of trade and corruption in oil exporting countries. And the last part presents the results of the research and assessment data results presented in the third part expose, that a decrease in corruption in the exporting country improves trade and on the importer side, a decrease in corruption will induce an increase in trade volume.